β-Arrestin-biased agonists of the GLP-1 receptor from β-amino acid residue incorporation into GLP-1 analogues - Hager, Marlies V. (J Am Chem Soc, 2016)
Activation of a G protein-coupled receptor (GPCR) causes recruitment of multiple intracellular proteins, each of which can activate distinct signaling pathways. This complexity has engendered interest in agonists that preferentially stimulate subsets among the natural signaling pathways (“biased agonists”). We have examined analogues of glucagon-like peptide-1 (GLP-1) containing β-amino acid residues in place of native α residues at selected sites and found that some analogues differ from GLP-1 in terms of their relative abilities to promote G protein activation (as monitored via cAMP production) versus β-arrestin recruitment (as monitored via BRET(2) assays). The α→β replacements generally cause modest declines in stimulation of cAMP production and β-arrestin recruitment, but for some replacement sets cAMP production is more strongly affected than is β-arrestin recruitment. The central portion of GLP-1 appears to be critical for achieving bias toward β-arrestin recruitment. These results suggest that backbone modification via α→β residue replacement may be a versatile source of agonists with biased GLP-1R activation profiles.